The Post-Mortem Disposition of Digital Assets: Special Reference to its Regulation in Latin America - Ordelin Font, Jorge Luis (2019)
At present, digital goods are part of the patrimony of people, however, not all legal systems have regulated what will be the fate of these after the death of their owner. The objective of this article is to establish the need for legal regulation of the disposition mortis causa of digital goods, based on the importance of such regulation in the relationships of users and service providers. To provide greater legal protection for digital goods, postmortem regulation is necessary, considering the different types of digital goods, its transmission and disposition after the death of its owner, as well as the obligations of the service providers in the fulfillment of these and their registry effectiveness. This regulation is essential in the current Latin American context.American context. the current LatinAmerican context.